Eficiência nutricional da dieta de novilhos de corte mantidos em pastagem associada a suplementação - Araujo, Tiago Luís Da Ros de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the intake, digestibility, performance and ruminal parameters of Nellore steers in rainy and dry season. For this two experiments was conducted, the experiment 1 were evaluated three levels of supplementation (1.0, 1.5 and 2.0% of body weight (BW)) in Brachiaria brizantha cv. Marandu from September to December 2011. The experiment 2 were evaluated the effects of three heights (15, 25 and 35 cm) of pasture Brachiaria brizantha cv. Marandu associated with mineral supplementation or multiple supplement with protein and energy (0.3 or 0.6% of PC) on intake, digestibility, ruminal fermentation and metabolic parameters of Nellore steers in January to April 2013. In experiment 1 the increase supplement level in the diet caused by the replacement effect of forage supplement and the total digestible nutrients increased linearly with the increase supplement level. To dry matter digestibility was observed opposite effect, with increasing supplement level occurred linear reduction of the apparent digestibility of the dry matter. The animal performance, there was a linear increase in average daily gain (ADG) due to the increase of supplementation level, 0.778; 1.054 and 1.096 kg / day, in treatments 1.0; 1.5 and 2.0 %BW respectively. Higher ADG increased linearly carcass yield, 54.3, 55.2, and 56.0% in response to increased supplement level. It can be concluded that the increase in the supplement level reduces forage intake increases the average daily gain and carcass yield. Supplementation of 1.5% BW has increased productivity, however supplementation level of 2.0% BW has a potential increase in stocking rate due to reduced forage intake. The experiment 2 in the pastures of 15 cm animals were supplemented with multiple supplement, 0.3 and 0.6% BW, and pastures of 25 and 35 cm were used mineral mixture ad libitum and 0.3% BW multiple supplement, amounting to six treatments. 12 canullated Nellore steers ...

Objetivou-se com este trabalho avaliar o consumo, a digestibilidade, o desempenho e parâmetros ruminais de novilhos da raça Nelore no período chuvoso e seco. Para isso realizou-se dois experimentos, no experimento 1 foram avaliados três níveis de suplementação (1,0, 1,5 e 2,0% do peso corporal (PC)) em pastagem de Brachiaria brizantha cv. Marandu no período de setembro a dezembro de 2011. No experimento 2 avaliou-se os efeitos de três alturas (15, 25 e 35 cm) de pasto Brachiaria brizantha cv. Marandu associados a suplementação com mistura mineral ou proteico energético (0,3 ou 0,6% do PC) sobre o consumo, digestibilidade, fermentação ruminal e parâmetros metabólicos de novilhos Nelore castrados nos meses de janeiro a abril de 2013. No experimento 1 o aumento do nível de suplemento na dieta acarretou efeito substitutivo da forragem pelo suplemento e o consumo de nutrientes digestíveis totais aumentou linearmente acompanhando o aumento do nível de suplemento. Em relação a digestibilidade da matéria seca observou-se efeito contrário, com o aumento do nível de suplemento ocorreu redução linear da digestibilidade aparente da dieta. Em relação ao desempenho animal, registrou-se aumento linear no ganho média diário (GMD) em virtude do aumento nos níveis de suplementação, 0,778; 1,054 e 1,096 kg/dia, nos tratamentos 1,0; 1,5 e 2,0 %PC respectivamente. Relacionado ao maior GMD, o rendimento de carcaça aumentou linearmente, 54,3, 55,2, e 56,0 % em resposta ao aumento do nível de suplemento. Pode-se concluir que o aumento no nível de suplemento reduz o consumo de forragem, aumenta o ganho médio diário e o rendimento de carcaça. A suplementação de 1,5% do PC apresenta maior produtividade, entretanto a suplementação ao nível de 2,0% do PC apresenta um potencial aumento na taxa de lotação em função da redução do consumo de forragem. No experimento 2 nos pastos de 15 cm os animais foram suplementados com...
Keywords: Bovino de corte - Nutrição; Desempenho; Pastagens; Forragem; Suplementos dieteticos; Forage